Penegakan Hukum Terkait Netralitas Aparatur Sipil Negara Dalam Pelaksanaan Pemilihan Kepala Daerah di Kota Bitung - Nathan Samuel Victor Pesak; Jacobus Ronald Mawuntu; Donna Okthalia Setiabudhi (Departement of Mathematics Education, 2023)
ASN neutrality in elections actually does not cause a loss of political rights either to run as a candidate or to vote. ASN neutrality is more likely for limited involvement of the bureaucracy in socializing or campaigning for certain candidates or political parties. This is intended to make ASN still able to separate its position as ASN which has an important position as a state administration officer. Considering that ASNs are carrying out their duties to serve the needs of the community in relation to certain parties, including in elections or local elections, this has the potential to influence or even pressure the community to follow the direction of support. Apart from that, of course there are concerns about prohibiting support for the opposing party Law Number 5 of 2014 Concerning State Civil Apparatus (UU ASN) does not include the offense of violating ASN neutrality in the prohibition nomenclature but is regulated in principles (principles) and obligations, however principles and obligations can also be interpreted as prohibitions because anyone who is subject to a definite obligation also subject to restrictions to comply with these obligations. Apart from not formulating a prohibition offense, the ASN Law also does not formulate in too much detail the principles or obligations that bind ASN. The formulation of offenses in the ASN Law is still very general in nature and requires details of the derivative regulations, therefore the author invites readers to look at the derivative regulations, including Government Regulation Number 53 of 2010, which was amended to Government Regulation Number 94 of 2021 concerning Civil Servant Discipline and Regulations Government Number 42 of 2004 concerning the Development of the Corps Spirit and Code of Ethics for Civil Servants, and other derivative regulations issued by the government, the President and by ministries.